Pressure sensor, sole three-point pressure sensing intelligent insole based on pressure sensor, method and application
The pressure sensor prepared by using Li/Al-LDH enhanced polyacrylamide/xanthan gum dual network nanoconductive hydrogels solves the problems of rigidity of traditional pressure sensors and degradation of hydrogels in dry environments, and achieves high sensitivity and stable monitoring of plantar pressure distribution.
Patent Information
- Application Number
- CN202411481398.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-04
AI Technical Summary
Existing pressure sensors mostly use rigid materials and cannot be bent, which limits their application in human body detection; hydrogel pressure sensors are prone to water loss in dry environments or after long-term use, resulting in device degradation or failure; traditional plantar pressure distribution monitoring equipment has limited use range, poor sensitivity, and low integration.
Using a pressure sensor based on Li/Al-LDH enhanced polyacrylamide/xanthan gum dual network nanoconductive hydrogel (PXL), a pressure sensor with a sandwich sandwich structure is formed through specific preparation methods and structural design, and it is applied to the three-point pressure sensing smart insole of the sole.
It achieves extremely high sensitivity and detection accuracy for pressure on the basis of ensuring flexibility, good linearity in resistance changes, and excellent pressure-sensitive characteristics in response/recovery time, repeatability, stability, etc. It is suitable for monitoring the foot pressure distribution, solving the problems of limited use range and poor sensitivity of traditional equipment.
Smart Images

Figure CN119555246A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials and electronic information technology, and in particular to a pressure sensor, a three-point pressure sensing intelligent insole based on the same, a method and an application thereof. Background Art
[0002] With the continuous improvement of the quality of life, people pay more and more attention to the monitoring of sports health status. Unhealthy and unscientific sports methods often cause damage to body functions. In the long run, they accumulate and form diseases, causing trouble to people's physical health. As one of the important biological signals of the human body, the plantar pressure distribution state can reflect a lot of information about the health status of human sports. Therefore, detecting the plantar pressure distribution state under various sports states is a very effective method to achieve sports health monitoring. Plantar pressure distribution monitoring can help prevent foot diseases such as valgus, Achilles tendonitis, plantar fasciitis and diabetic foot. Traditional plantar pressure distribution monitoring requires the connection of large medical equipment, which is expensive, limits the user's range of activities, and is not conducive to daily use at home; and traditional pressure sensors are mostly based on rigid materials such as ceramics, silicon or metals. Electronic devices with such rigid substrates cannot be bent, which greatly limits their application in human body detection. Therefore, the development of a plantar pressure sensing device based on a flexible substrate pressure sensor has become a new research hotspot.
[0003] Pressure-sensitive materials are the core components of pressure sensors and largely determine the performance of pressure sensors. Nano-conductive hydrogel, as a flexible conductive organic material, has excellent linearity to changes in pressure and is one of the excellent flexible pressure-sensitive materials. Polyacrylamide (PAM), as an excellent polymer material, has abundant hydrophilic groups that give it excellent hydrophilic properties, and its preparation method is simple and low-cost, making it an excellent non-conductive polymer matrix for hydrogels. In addition, xanthan gum (XG), as a biocompatible natural polysaccharide with an ordered rigid double helix chain structure, can form a semi-interpenetrating network structure when combined with PAM, greatly enhancing the mechanical properties of the hydrogel. At the same time, Li / Al-LDH, because of its rich surface metal ions, can form coordination bonds with the groups on PAM and XG, which not only gives the hydrogel excellent conductivity but also enhances the mechanical properties of the hydrogel again. It is one of the excellent nano-conductive fillers for hydrogels. Therefore, the pressure sensor based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nanoconductive hydrogel (PXL) has extremely high sensitivity and detection accuracy to pressure while ensuring flexibility, and has good linearity in resistance change within the pressure range. It also exhibits excellent pressure-sensitive properties in terms of response / recovery time, repeatability, stability, etc., giving full play to the advantages of the pressure sensor.
[0004] At present, the pressure sensor in the prior art has the following defects:
[0005] 1. Most existing pressure sensors use rigid materials such as ceramics, silicon or metal as substrates. Such rigid substrates cannot be bent, are not flexible, and have poor shape adaptability when integrated into different devices.
[0006] 2. Currently, long-term exposure of hydrogel pressure sensors to dry environments or long-term use usually causes water loss on the sensor's pressure-sensitive material, leading to device degradation or failure.
[0007] 3. The common plantar pressure distribution monitoring devices currently on the market have the disadvantages of limited scope of use, poor sensitivity, and low integration. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide a pressure sensor, a three-point pressure sensing intelligent insole based on the same, a method and an application thereof.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] A pressure sensor based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano conductive hydrogel (PXL), comprising the following steps:
[0011] Step 1, dissolving LiCl, AlCl3 and urea in deionized water, mechanically stirring until they are completely dissolved, to obtain a Li / Al-LDH precursor solution;
[0012] Step 2, placing the Li / Al-LDH precursor solution in a reflux device for reflux, using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0013] Step 3, adding the freshly prepared Li / Al-LDH solution with Tyndall effect and deionized water into a beaker, and then slowly adding acrylamide AM monomer and xanthan gum XG powder thereto, stirring magnetically and then performing ultrasonic treatment in an ice water bath to remove bubbles, to obtain a microemulsion viscous liquid;
[0014] Step 4, adding a photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) and a crosslinking agent N,N-methylenebisacrylamide MBA, mixing and magnetically stirring to obtain a PXL hydrogel precursor solution;
[0015] Step 5, quickly transferring the PXL hydrogel precursor solution into a polytetrafluoroethylene (PTFE) mold, and polymerizing in situ under ultraviolet light to obtain the PXL nano conductive hydrogel;
[0016] Step 6, mixing the A glue and the B glue of polydimethylsiloxane (PDMS), stirring mechanically to make them uniform, and removing bubbles by ultrasound to obtain a PDMS precursor solution;
[0017] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at high temperature to obtain a PDMS film;
[0018] Step 8: Cut the prepared PDMS film into squares, and then assemble it with the PXL nano-conductive hydrogel. After assembly, fix the wires at both ends to achieve electrical connectivity, and finally obtain a pressure sensor with a sandwich structure based on the PXL nano-conductive hydrogel.
[0019] Further, the ratio of LiCl:AlCl3:urea:deionized water added in step 1 was 1:3.2:14.4:50 g:g:g:mL, wherein AlCl3 was slowly added in the fume hood at the end and mechanically stirred for 15 min to obtain a Li / Al-LDH precursor solution;
[0020] Alternatively, the temperature of the reflux device in step 2 is controlled at 97°C.
[0021] Furthermore, the total volume of the Li / Al-LDH solution with Tyndall effect and deionized water added in step 3 and the ratio of acrylamide to g are 20:3, and the ratio of acrylamide to xanthan gum is 3:0.15; magnetic stirring is performed for 6 hours; the ice water bath temperature is 0°C, and the ultrasonic frequency is 10kHz for 10 minutes to remove bubbles, and a microemulsion viscous liquid is obtained. By controlling the amount of Li / Al-LDH solution, PXL with different Li / Al-LDH contents can be obtained. n (n is the mass fraction of Li / Al-LDH in the hydrogel, 3.33, 6.67, 13.33, 16.67%) nanoconductive hydrogel.
[0022] Furthermore, the ratio of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone: N,N-methylenebisacrylamide: acrylamide added in step 4 was 9:2.4:3 in mg:mg:g; magnetic stirring was performed for 1 hour to obtain PXL n Hydrogel precursor solution.
[0023] Furthermore, in step 5, PXL n After the hydrogel precursor solution is quickly transferred to the polytetrafluoroethylene mold, it should be covered with a glass slide to isolate oxygen; it should be irradiated under a 20W ultraviolet lamp with a wavelength of 365nm for 30 minutes to obtain PXL in situ polymerization. nNano conductive hydrogel; its shape is a cylindrical hydrogel with a diameter of 25mm and a height of 5mm.
[0024] Furthermore, in step 6, the volume ratio of A glue and B glue of polydimethylsiloxane (PDMS) is 10:1, wherein A glue is dimethylsiloxane and B glue is a crosslinking agent and accelerator; mechanical stirring is performed for 2 hours; ultrasonic treatment is performed at a frequency of 10 kHz for 30 minutes to remove bubbles, and a PDMS precursor solution is obtained;
[0025] Alternatively, in step 7, the temperature of the vacuum oven is controlled at 50° C., and high-temperature curing is performed for 12 hours to obtain a PDMS film.
[0026] Furthermore, the size of the PDMS film cut in step 8 is a 3 cm × 3 cm square; the sandwich structure uses the PDMS film as the upper and lower dielectric layers, PXL n Nano-conductive hydrogel is used as the central sensing layer, and then the two ends are connected with wires to finally obtain PXL n Pressure sensor.
[0027] The pressure sensor as described above is used in a three-point pressure sensing smart insole for the sole of the foot.
[0028] The three-point pressure sensing intelligent insole for the sole of the foot is made by using the pressure sensor as described above, and the assembly method of the three-point pressure sensing intelligent insole for the sole of the foot comprises the following steps:
[0029] By designing copper wire circuits and PXL n The hydrogel is assembled and then sealed with a plastic film using PET as the base material and EVA as the adhesive to form an insole; then it is connected to an AD converter, a single-chip computer, a Bluetooth module, a voltage regulator module and a lithium battery through wires; finally, the program is written to obtain a three-point pressure-sensing smart insole for the sole of the foot.
[0030] The functional APP of the three-point pressure-sensing smart insole for the sole as described above can monitor the pressure distribution state of the user's sole in real time through a mobile phone, evaluate the user's sports health, and thus achieve disease prevention.
[0031] The advantages and positive effects achieved by the present invention are:
[0032] 1. The polyacrylamide (PAM) used in the present invention is an excellent polymer material. Its abundant hydrophilic groups give it excellent hydrophilic properties. Its preparation method is simple and the cost is low. It is an excellent non-conductive polymer matrix for hydrogels.
[0033] 2. Xanthan gum (XG) used in the present invention is a biocompatible natural polysaccharide with an ordered rigid double helix chain structure. When combined with PAM, it can form a semi-interpenetrating network structure, greatly enhancing the mechanical properties of the hydrogel.
[0034] 3. The Li / Al-LDH obtained in the present invention can form coordination bonds with the groups on PAM and XG because of its rich metal ions on the surface, which not only gives the hydrogel excellent conductivity but also further enhances the mechanical properties of the hydrogel. It is one of the excellent nano-conductive fillers for hydrogel.
[0035] 4. The pressure sensor based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel (PXL) obtained in the present invention has extremely high sensitivity and detection accuracy to pressure while ensuring flexibility, and has good linearity in resistance change within the pressure range, and exhibits excellent pressure-sensitive characteristics in response / recovery time, repeatability, stability, etc., giving full play to the advantages of the pressure sensor.
[0036] 5. The three-point pressure sensing smart insole based on the PXL pressure sensor of the present invention is light and compact through integrated programming, and can monitor the plantar pressure distribution of the user in real time and accurately through the APP, making the plantar force monitoring more convenient and economical. The present invention assembles a three-point pressure sensing smart insole based on the PXL pressure sensor, which solves the problem that the traditional plantar pressure distribution monitoring equipment is bulky and expensive.
[0037] 6. The present invention has developed an APP for a three-point pressure sensing smart insole based on a PXL pressure sensor to solve the problem of limited activity area when using traditional plantar pressure distribution monitoring equipment.
[0038] 7. The present invention proposes a simple, green and innovative strategy to prepare Li / Al-LDH enhanced PAM / XG dual network nano-conductive hydrogel PXL. PAM is used as the main network, and natural biopolysaccharide XG extracted from microorganisms is used as the second network; using the freshly prepared Li / Al-LDH solution with Tyndall effect, AM is polymerized in situ on the surface of Li / Al-LDH nanosheets to form a Li / Al-LDH nanosheet cross-linked PAM conductive network, which not only gives the hydrogel conductivity, but also chemically and physically cross-links with the PAM / XG semi-interpenetrating network structure to enhance its mechanical and sensing properties. The unique multi-synergistic network gives PXL hydrogel excellent mechanical properties.
[0039] 8. The pressure sensor based on PXL nano-conductive hydrogel prepared by the present invention can be used to monitor different pressures of 0-15kPa. The results show that the sensor has good linearity in resistance change within the pressure range, and exhibits excellent pressure-sensitive properties in terms of sensitivity, response / recovery time, repeatability, stability, etc., and can still be used stably after being exposed at room temperature for seven days. In addition, the present invention also combines it with electronic components such as single-chip microcomputers and Bluetooth modules, assembles it into a three-point pressure sensing smart insole for the sole after programming, and monitors the distribution of sole pressure in real time through the developed APP.
[0040] 9. The PXL pressure sensor in the present invention is applied to the three-point pressure sensing intelligent insole of the sole, and it also needs to be matched with electronic components such as a single-chip microcomputer and a Bluetooth module. As a single-chip microcomputer based on the ARM Cortex-M core, the STM32 single-chip microcomputer has the following advantages: fast running speed and strong performance; low power consumption design, suitable for battery-powered applications; support for multiple bus interfaces, such as CAN, SPI, I2C, etc.; rich peripherals, such as ADC, DAC, PWM, USART, USB, etc.; integrated with multiple functional modules, such as clock module, interrupt controller, power management, etc.; perfect development tool chain, support for multiple development environments, such as Keil, IAR, GCC, etc. In addition, as a low-cost Bluetooth module, JDY-31 has the characteristics of strong compatibility, stable communication, flexible and convenient use, and excellent hardware design. It has very accurate remote real-time data transmission capabilities when matched with the independently developed plantar pressure distribution monitoring APP. Therefore, the programmed and assembled three-point pressure sensing smart insole based on the PXL pressure sensor can monitor the user's plantar pressure distribution in real time and accurately through the APP, and perform sports health identification and disease prevention, making plantar force monitoring more convenient and economical.
[0041] 10. The pressure sensor of the present invention has high flexibility, water retention and stability. The resistance signal value output by the sensor manufactured in the present invention can remain stable after being exposed at room temperature for seven days.
[0042] The design of the pressure sensor based on PXL nano-conductive hydrogel in the present invention solves the problem of poor bonding between the conductive filler and the hydrogel substrate to a great extent, so that the hydrogel can still maintain excellent conductivity during the process of force deformation, effectively avoiding the problem of unstable and lost sensing signals.
[0043] The pressure sensor of the present invention has the advantages of high integration, fast response and portability. So far, the fastest response recovery time of the sensor manufactured by the present invention to respond to and recover from pressure is 500 milliseconds.
[0044] In summary, the pressure sensor of the present invention can solve the technical problems existing in the prior art.
[0045] 11. The pressure sensor based on PXL nano-conductive hydrogel in the present invention has extremely high sensitivity and detection accuracy to pressure while ensuring flexibility, and has good linearity in resistance change within the pressure range, and exhibits excellent pressure-sensitive characteristics in terms of response / recovery time, repeatability, stability, etc., giving full play to the advantages of the pressure sensor. After being applied to the three-point pressure sensing smart insole on the sole, the integrated programming makes the smart insole light, compact and easy to wear, and can detect the user's real-time sole pressure distribution through the APP, making sports health monitoring and disease prevention more convenient and economical. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The red laser pen irradiation phenomenon diagrams of the Li / Al-LDH solution in the present invention corresponding to different storage time; wherein the first row is the red laser pen irradiation phenomenon corresponding to the freshly prepared Li / Al-LDH solution, the Li / Al-LDH solution after being stored for one week and the Li / Al-LDH solution after being stored for one month; the second row is the red laser pen irradiation phenomenon corresponding to the freshly prepared Li / Al-LDH solution, the Li / Al-LDH solution after being stored for one week and the Li / Al-LDH solution after being stored for one month;
[0047] Figure 2 A schematic diagram of a manufacturing process of the PXL nano-conductive hydrogel in the present invention;
[0048] Figure 3 The sandwich structure diagram of the PXL pressure sensor in the present invention;
[0049] Figure 4 These are SEM images of different hydrogels obtained in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;
[0050] Figure 5 The PXL obtained in Example 1 of the present invention 13.33% TEM image and element distribution map of nano-conductive hydrogel;
[0051] Figure 6 The infrared spectra of different hydrogels obtained in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;
[0052] Figure 7 The PXL obtained in Example 1 of the present invention 13.33% XRD pattern of hydrogel;
[0053] Figure 8 The tensile stress-strain curves of the hydrogels of different components prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Example 1 and Comparative Example 5 of the present invention and the PXL prepared in Example 1 are shown in FIG. 13.33%Various compressive mechanical properties test diagrams of the pressure sensor; (a) is the tensile stress-strain curve of hydrogels of different components, and (b) is the PXL prepared in Example 1 13.33% Compressive stress diagram of the pressure sensor under 0-80% strain, (c) is the PXL prepared in Example 1 13.33% Compressive stress diagram of the pressure sensor at different compression rates under 80% strain, (d) is the PXL prepared in Example 1 13.33% Compressive stress diagram of the pressure sensor at different dwell times at 60% strain;
[0054] Fig. 9 The PXL prepared in Example 1 of the present invention 13.33% Various compression electrical performance test diagrams of pressure sensors;
[0055] Fig.10 The PXL prepared in Example 1 and Example 2 of the present invention is placed for seven days. 13.33% Tensile stress-strain curve of the hydrogel and the PXL prepared in Example 2 after seven days of storage 13.33% Electrical performance test diagram of pressure sensor;
[0056] Fig.11 This is an overall connection framework diagram of the three-point pressure sensing intelligent insole based on the PXL pressure sensor in the present invention;
[0057] Fig.12 This is a real-time plantar pressure distribution status monitoring diagram of the APP of the three-point plantar pressure sensing smart insole based on the PXL pressure sensor in the present invention. DETAILED DESCRIPTION
[0058] The present invention will be further described below in conjunction with the embodiments. The following embodiments are descriptive rather than restrictive, and the protection scope of the present invention cannot be limited by the following embodiments.
[0059] The various experimental operations involved in the specific embodiments are all routine techniques in the art. For parts not specially annotated in this document, ordinary technicians in the art can implement them by referring to various commonly used reference books, scientific and technological literature or related instructions, manuals, etc. before the filing date of this invention.
[0060] A pressure sensor based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano conductive hydrogel (PXL), comprising the following steps:
[0061] Step 1, dissolving LiCl, AlCl3 and urea in deionized water, mechanically stirring until they are completely dissolved, to obtain a Li / Al-LDH precursor solution;
[0062] Step 2, placing the Li / Al-LDH precursor solution in a reflux device for reflux, using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0063] Step 3, adding the freshly prepared Li / Al-LDH solution with Tyndall effect and deionized water into a beaker, and then slowly adding acrylamide AM monomer and xanthan gum XG powder thereto, stirring magnetically and then performing ultrasonic treatment in an ice water bath to remove bubbles, to obtain a microemulsion viscous liquid;
[0064] Step 4, adding a photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) and a crosslinking agent N,N-methylenebisacrylamide MBA, mixing and magnetically stirring to obtain a PXL hydrogel precursor solution;
[0065] Step 5, quickly transferring the PXL hydrogel precursor solution into a polytetrafluoroethylene (PTFE) mold, and polymerizing in situ under ultraviolet light to obtain the PXL nano conductive hydrogel;
[0066] Step 6, mixing the A glue and the B glue of polydimethylsiloxane (PDMS), stirring mechanically to make them uniform, and removing bubbles by ultrasound to obtain a PDMS precursor solution;
[0067] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at high temperature to obtain a PDMS film;
[0068] Step 8: Cut the prepared PDMS film into squares, and then assemble it with the PXL nano-conductive hydrogel. After assembly, fix the wires at both ends to achieve electrical connectivity, and finally obtain a pressure sensor with a sandwich structure based on the PXL nano-conductive hydrogel.
[0069] Preferably, the ratio of LiCl:AlCl3:urea:deionized water added in step 1 is 1:3.2:14.4:50 g:g:g:mL, wherein AlCl3 is slowly added in a fume hood at the end and mechanically stirred for 15 min to obtain a Li / Al-LDH precursor solution;
[0070] Alternatively, the temperature of the reflux device in step 2 is controlled at 97°C.
[0071] Preferably, the total volume of the Li / Al-LDH solution with Tyndall effect and deionized water added in step 3 is 20:3 in mL:g to acrylamide, and the ratio of acrylamide to xanthan gum is 3:0.15 in g:g; magnetic stirring is performed for 6 hours; the ice-water bath temperature is 0°C, and the ultrasonic frequency is 10kHz for 10 minutes to remove bubbles, thereby obtaining a microemulsion viscous liquid. By controlling the amount of Li / Al-LDH solution, PXL with different Li / Al-LDH contents can be obtained. n (n is the mass fraction of Li / Al-LDH in the hydrogel, 3.33, 6.67, 13.33, 16.67%) nanoconductive hydrogel.
[0072] Preferably, the ratio of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone: N,N-methylenebisacrylamide: acrylamide added in step 4 is 9:2.4:3 in mg:mg:g; magnetic stirring is performed for 1 hour to obtain PXL n Hydrogel precursor solution.
[0073] Preferably, in step 5, PXL n After the hydrogel precursor solution is quickly transferred to the polytetrafluoroethylene mold, it should be covered with a glass slide to isolate oxygen; it should be irradiated under a 20W ultraviolet lamp with a wavelength of 365nm for 30 minutes to obtain PXL in situ polymerization. n Nano conductive hydrogel; its shape is a cylindrical hydrogel with a diameter of 25mm and a height of 5mm.
[0074] Preferably, in step 6, the volume ratio of A glue and B glue of polydimethylsiloxane (PDMS) is 10:1, wherein A glue is dimethylsiloxane and B glue is a crosslinking agent and accelerator; mechanical stirring is performed for 2 hours; ultrasonic treatment is performed at a frequency of 10 kHz for 30 minutes to remove bubbles, and a PDMS precursor solution is obtained;
[0075] Alternatively, in step 7, the temperature of the vacuum oven is controlled at 50° C., and high-temperature curing is performed for 12 hours to obtain a PDMS film.
[0076] Preferably, the size of the PDMS film cut in step 8 is a 3 cm × 3 cm square; the sandwich structure uses the PDMS film as the upper and lower dielectric layers, the PXL n Nano-conductive hydrogel is used as the central sensing layer, and then the two ends are connected with wires to finally obtain PXL n Pressure sensor.
[0077] The pressure sensor as described above is used in a three-point pressure sensing smart insole for the sole of the foot.
[0078] The three-point pressure sensing intelligent insole for the sole of the foot is made by using the pressure sensor as described above, and the assembly method of the three-point pressure sensing intelligent insole for the sole of the foot comprises the following steps:
[0079] By designing copper wire circuits and PXL n The hydrogel is assembled and then sealed with a plastic film using PET as the base material and EVA as the adhesive to form an insole; then it is connected to an AD converter, a single-chip computer, a Bluetooth module, a voltage regulator module and a lithium battery through wires; finally, the program is written to obtain a three-point pressure-sensing smart insole for the sole of the foot.
[0080] The functional APP of the three-point pressure-sensing smart insole for the sole as described above can monitor the pressure distribution state of the user's sole in real time through a mobile phone, evaluate the user's sports health, and thus achieve disease prevention.
[0081] Specifically, the relevant preparation and detection are as follows:
[0082] Example 1
[0083] A Li / Al-LDH-enhanced polyacrylamide / xanthan gum double network nanoconductive hydrogel (PXL 13.33% ) is a method for preparing a pressure sensor, the method comprising the following steps:
[0084] Step 1: Dissolve LiCl (1 g) and urea (14.4 g) in deionized water (50 mL), then slowly add AlCl3 (3.2 g) in a fume hood, and mechanically stir for 15 min until it is completely dissolved to obtain a Li / Al-LDH precursor solution;
[0085] Step 2, placing the Li / Al-LDH precursor solution in a reflux device, reflux at 97° C., using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0086] Step 3: Add the freshly prepared Li / Al-LDH solution (10 mL) with Tyndall effect and deionized water (10 mL) into a beaker, then slowly add acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) thereto, stir magnetically for 6 h, and then perform ultrasonic treatment at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, to obtain a microemulsion viscous liquid;
[0087] Step 4: Add photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mix and stir magnetically for 1 h to obtain PXL 13.33% Hydrogel precursor solution;
[0088] Step 5: PXL 13.33% The hydrogel precursor solution was quickly transferred to a polytetrafluoroethylene (PTFE) mold, and then covered with a glass slide to isolate oxygen. The mold was then irradiated under a 20W UV lamp with a wavelength of 365nm for 30 minutes, and in-situ polymerization was performed to obtain a cylindrical PXL with a diameter of 25mm and a height of 5mm. 13.33% Nano-conductive hydrogel;
[0089] Step 6, polydimethylsiloxane (PDMS) A glue (dimethylsiloxane) and B glue (crosslinking agent and accelerator) are mixed in a volume ratio of 10:1, mechanically stirred for 2 hours, and then ultrasonically treated at a frequency of 10 kHz for 30 minutes to remove bubbles, thereby obtaining a PDMS precursor solution;
[0090] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at 50° C. for 12 hours to obtain a PDMS film;
[0091] Step 8: Cut the prepared PDMS film into squares of 3 cm × 3 cm, and then assemble it with the PXL nano-conductive hydrogel, using the PDMS film as the upper and lower dielectric layers and the PXL 13.33% Nano-conductive hydrogel is used as the central sensing layer. After assembly, the wires are fixed at both ends to achieve electrical connectivity, and finally the PXL-based 13.33% Sandwich structure pressure sensor of nano-conductive hydrogel;
[0092] Based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel (PXL 13.33% ) pressure sensor.
[0093] Example 2
[0094] A Li / Al-LDH-enhanced polyacrylamide / xanthan gum double network nanoconductive hydrogel (PXL) after being placed at room temperature for seven days 13.33% ) is a method for preparing a pressure sensor, the method comprising the following steps:
[0095] Step 1: Dissolve LiCl (1 g) and urea (14.4 g) in deionized water (50 mL), then slowly add AlCl3 (3.2 g) in a fume hood, and mechanically stir for 15 min until it is completely dissolved to obtain a Li / Al-LDH precursor solution;
[0096] Step 2, placing the Li / Al-LDH precursor solution in a reflux device, reflux at 97° C., using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0097] Step 3: Add the freshly prepared Li / Al-LDH solution (10 mL) with Tyndall effect and deionized water (10 mL) into a beaker, then slowly add acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) thereto, stir magnetically for 6 h, and then perform ultrasonic treatment at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, to obtain a microemulsion viscous liquid;
[0098] Step 4: Add photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mix and stir magnetically for 1 h to obtain PXL 13.33% Hydrogel precursor solution;
[0099] Step 5: PXL 13.33% The hydrogel precursor solution was quickly transferred to a polytetrafluoroethylene (PTFE) mold, and then covered with a glass slide to isolate oxygen. The mold was then irradiated under a 20W UV lamp with a wavelength of 365nm for 30 minutes, and in-situ polymerization was performed to obtain a cylindrical PXL with a diameter of 25mm and a height of 5mm. 13.33% Nano-conductive hydrogel;
[0100] Step 6, polydimethylsiloxane (PDMS) A glue (dimethylsiloxane) and B glue (crosslinking agent and accelerator) are mixed in a volume ratio of 10:1, mechanically stirred for 2 hours, and then ultrasonically treated at a frequency of 10 kHz for 30 minutes to remove bubbles, thereby obtaining a PDMS precursor solution;
[0101] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at 50° C. for 12 hours to obtain a PDMS film;
[0102] Step 8: Cut the prepared PDMS film into squares of 3 cm × 3 cm, and then assemble it with the PXL nano-conductive hydrogel, using the PDMS film as the upper and lower dielectric layers and the PXL 13.33% Nano-conductive hydrogel is used as the central sensing layer. After assembly, the wires are fixed at both ends to achieve electrical connectivity, and finally the PXL-based 13.33% Sandwich structure pressure sensor of nano-conductive hydrogel;
[0103] Step 9: Place the pressure sensor at room temperature of 25°C in a ventilated state for seven days;
[0104] That is, after being placed at room temperature for seven days, the Li / Al-LDH-enhanced polyacrylamide / xanthan gum double network nanoconductive hydrogel (PXL 13.33% ) pressure sensor.
[0105] Comparative Example 1
[0106] This comparative example is a method for preparing pure PAM hydrogel, which comprises the following steps:
[0107] Step 3, deionized water (20 mL) was added to a beaker, and then acrylamide (AM) monomer (3 g) was slowly added thereto, and after magnetic stirring for 6 h, ultrasonic treatment was performed at a frequency of 10 kHz for 10 min in a 0° C. ice water bath to remove bubbles, to obtain a transparent liquid;
[0108] Step 4, adding photoinitiator Irgacure 2959 (9 mg) and crosslinking agent MBA (2.4 mg), mixing and magnetically stirring for 1 h to obtain a PAM hydrogel precursor solution;
[0109] Step 5, after the PAM hydrogel precursor solution is quickly transferred to a polytetrafluoroethylene (PTFE) mold, it is tightly sealed with a glass slide to isolate oxygen, and irradiated under a UV lamp with a power of 20 W and a wavelength of 365 nm for 30 minutes, and a cylindrical PAM hydrogel with a diameter of 25 mm and a height of 5 mm is obtained after polymerization;
[0110] That is, pure PAM hydrogel.
[0111] Comparative Example 2
[0112] This comparative example is a method for preparing PX hydrogel, which comprises the following steps:
[0113] Step 3, deionized water (20 mL) was added to a beaker, and then acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) were slowly added thereto, and after magnetic stirring for 6 h, ultrasonic treatment was performed at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, thereby obtaining a transparent viscous liquid;
[0114] Step 4, adding photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mixing and magnetically stirring for 1 h to obtain a PX hydrogel precursor solution;
[0115] Step 5, after the PX hydrogel precursor solution is quickly transferred to a polytetrafluoroethylene (PTFE) mold, it is tightly sealed with a glass slide to isolate oxygen, and irradiated under a UV lamp with a power of 20 W and a wavelength of 365 nm for 30 min. After polymerization, a cylindrical PX hydrogel with a diameter of 25 mm and a height of 5 mm is obtained;
[0116] That is, PX hydrogel.
[0117] Comparative Example 3
[0118] This comparative example is based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano conductive hydrogel (PXL 3.33% ) is a method for preparing a pressure sensor, the method comprising the following steps:
[0119] Step 1: Dissolve LiCl (1 g) and urea (14.4 g) in deionized water (50 mL), then slowly add AlCl3 (3.2 g) in a fume hood, and mechanically stir for 15 min until it is completely dissolved to obtain a Li / Al-LDH precursor solution;
[0120] Step 2, placing the Li / Al-LDH precursor solution in a reflux device, reflux at 97° C., using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0121] Step 3: Add the freshly prepared Li / Al-LDH solution (2.5 mL) with Tyndall effect and deionized water (17.5 mL) into a beaker, then slowly add acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) thereto, stir magnetically for 6 h, and then perform ultrasonic treatment at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, to obtain a microemulsion viscous liquid;
[0122] Step 4: Add photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mix and stir magnetically for 1 h to obtain PXL 3.33% Hydrogel precursor solution;
[0123] Step 5: PXL 3.33% The hydrogel precursor solution was quickly transferred to a polytetrafluoroethylene (PTFE) mold, and then covered with a glass slide to isolate oxygen. The mold was then irradiated under a 20W UV lamp with a wavelength of 365nm for 30 minutes, and in-situ polymerization was performed to obtain a cylindrical PXL with a diameter of 25mm and a height of 5mm. 3.33% Nano-conductive hydrogel;
[0124] Step 6, polydimethylsiloxane (PDMS) A glue (dimethylsiloxane) and B glue (crosslinking agent and accelerator) are mixed in a volume ratio of 10:1, mechanically stirred for 2 hours, and then ultrasonically treated at a frequency of 10 kHz for 30 minutes to remove bubbles, thereby obtaining a PDMS precursor solution;
[0125] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at 50° C. for 12 hours to obtain a PDMS film;
[0126] Step 8: Cut the prepared PDMS film into squares of 3 cm × 3 cm, and then assemble it with the PXL nano-conductive hydrogel, using the PDMS film as the upper and lower dielectric layers and the PXL 3.33% Nano-conductive hydrogel is used as the central sensing layer. After assembly, the wires are fixed at both ends to achieve electrical connectivity, and finally the PXL-based 3.33% Sandwich structure pressure sensor of nano-conductive hydrogel;
[0127] Based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel (PXL 3.33% ) pressure sensor.
[0128] Comparative Example 4
[0129] This comparative example is based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano conductive hydrogel (PXL 6.67% ) is a method for preparing a pressure sensor, the method comprising the following steps:
[0130] Step 1: Dissolve LiCl (1 g) and urea (14.4 g) in deionized water (50 mL), then slowly add AlCl3 (3.2 g) in a fume hood, and mechanically stir for 15 min until it is completely dissolved to obtain a Li / Al-LDH precursor solution;
[0131] Step 2, placing the Li / Al-LDH precursor solution in a reflux device, reflux at 97° C., using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0132] Step 3: Add the freshly prepared Li / Al-LDH solution (5 mL) with Tyndall effect and deionized water (15 mL) into a beaker, then slowly add acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) thereto, stir magnetically for 6 h, and then perform ultrasonic treatment at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, thereby obtaining a microemulsion-like viscous liquid;
[0133] Step 4: Add photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mix and stir magnetically for 1 h to obtain PXL 6.67% Hydrogel precursor solution;
[0134] Step 5: PXL 6.67%The hydrogel precursor solution was quickly transferred to a polytetrafluoroethylene (PTFE) mold, and then covered with a glass slide to isolate oxygen. The mold was then irradiated under a 20W UV lamp with a wavelength of 365nm for 30 minutes, and in-situ polymerization was performed to obtain a cylindrical PXL with a diameter of 25mm and a height of 5mm. 6.67% Nano-conductive hydrogel;
[0135] Step 6, polydimethylsiloxane (PDMS) A glue (dimethylsiloxane) and B glue (crosslinking agent and accelerator) are mixed in a volume ratio of 10:1, mechanically stirred for 2 hours, and then ultrasonically treated at a frequency of 10 kHz for 30 minutes to remove bubbles, thereby obtaining a PDMS precursor solution;
[0136] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at 50° C. for 12 hours to obtain a PDMS film;
[0137] Step 8: Cut the prepared PDMS film into squares of 3 cm × 3 cm, and then assemble it with the PXL nano-conductive hydrogel, using the PDMS film as the upper and lower dielectric layers and the PXL 6.67% Nano-conductive hydrogel is used as the central sensing layer. After assembly, the wires are fixed at both ends to achieve electrical connectivity, and finally the PXL-based 6.67% Sandwich structure pressure sensor of nano-conductive hydrogel;
[0138] Based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel (PXL 6.67% ) pressure sensor.
[0139] Comparative Example 5
[0140] This comparative example is based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano conductive hydrogel (PXL 16.67% ) is a method for preparing a pressure sensor, the method comprising the following steps:
[0141] Step 1: Dissolve LiCl (1 g) and urea (14.4 g) in deionized water (50 mL), then slowly add AlCl3 (3.2 g) in a fume hood, and mechanically stir for 15 min until it is completely dissolved to obtain a Li / Al-LDH precursor solution;
[0142] Step 2, placing the Li / Al-LDH precursor solution in a reflux device, reflux at 97° C., using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution;
[0143] Step 3: Add the freshly prepared Li / Al-LDH solution with Tyndall effect (12.5 mL) and deionized water (7.5 mL) into a beaker, then slowly add acrylamide (AM) monomer (3 g) and xanthan gum (XG) powder (0.15 g) thereto, stir magnetically for 6 h, and then perform ultrasonic treatment at a frequency of 10 kHz for 10 min in a 0°C ice water bath to remove bubbles, to obtain a microemulsion-like viscous liquid;
[0144] Step 4: Add photoinitiator Irgacure 2959 (9 mg) and crosslinker MBA (2.4 mg), mix and stir magnetically for 1 h to obtain PXL 16.67% Hydrogel precursor solution;
[0145] Step 5: PXL 16.67% The hydrogel precursor solution was quickly transferred to a polytetrafluoroethylene (PTFE) mold, and then covered with a glass slide to isolate oxygen. The mold was then irradiated under a 20W UV lamp with a wavelength of 365nm for 30 minutes, and in-situ polymerization was performed to obtain a cylindrical PXL with a diameter of 25mm and a height of 5mm. 16.67% Nano-conductive hydrogel;
[0146] Step 6, polydimethylsiloxane (PDMS) A glue (dimethylsiloxane) and B glue (crosslinking agent and accelerator) are mixed in a volume ratio of 10:1, mechanically stirred for 2 hours, and then ultrasonically treated at a frequency of 10 kHz for 30 minutes to remove bubbles, thereby obtaining a PDMS precursor solution;
[0147] Step 7, pouring the PDMS precursor solution into a polytetrafluoroethylene (PTFE) mold, and then placing it in a vacuum oven, and curing it at 50° C. for 12 hours to obtain a PDMS film;
[0148] Step 8: Cut the prepared PDMS film into squares of 3 cm × 3 cm, and then assemble it with the PXL nano-conductive hydrogel, using the PDMS film as the upper and lower dielectric layers and the PXL 16.67% Nano-conductive hydrogel is used as the central sensing layer. After assembly, the wires are fixed at both ends to achieve electrical connectivity, and finally the PXL-based 16.67% Sandwich structure pressure sensor of nano-conductive hydrogel;
[0149] Based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel (PXL 16.67% ) pressure sensor.
[0150] The ratios of PXL hydrogels with different Li / Al-LDH contents in the above embodiments and comparative examples can be shown in Table 1.
[0151] Table 1 Preparation ratio of PXL hydrogels with different Li / Al-LDH contents
[0152]
[0153] The relevant tests are as follows:
[0154] Figure 4 The microstructure of all hydrogels was characterized on a field emission high-resolution scanning electron microscope (FE-SEM) by Awavepreo from FEI Company (USA). Before observation, PAM, PX, and PXL hydrogels were freeze-dried and brittle fractured in liquid nitrogen, then coated with a thin gold film to avoid charging effects, and cross-sectional SEM images were observed.
[0155] Figure 5 The detection method is to observe the morphological characteristics and particle size of the samples using a transmission electron microscope (Thermo Fisher Scientific, USA). A small amount of powder sample is ultrasonically dispersed in ultrapure water / ethanol, 1-2 drops are dropped on a copper grid with a dropper, the floating liquid is absorbed with filter paper, and the floating material is allowed to stand until it is dry, and then placed under a 200kV transmission electron microscope (FEI-Talos F200 S) for photography.
[0156] Figure 6 The chemical composition of the hydrogel was analyzed by Fourier transform infrared spectroscopy (FT-IR) using a VECTOR 22 infrared spectrometer (Bruker, Germany). -1 Within the range of 4cm -1 The spectrum was obtained by averaging the signals from 32 scans at a resolution of 1.
[0157] Figure 7 The detection method is powder X-ray diffraction (XRD) data collected on a TD-3500 X-ray diffractometer (Dandong, China) at a voltage of 30 kV, a current of 15 mA, a scanning rate of 0.05° / s, and a 2θ range of 5° to 80°. The sample is a long film with a thickness of about 1 mm.
[0158] Figure 8 , Fig. 9 as well as Fig.10 The testing method is the compression and tensile mechanical properties of the hydrogels were measured at room temperature using a uniaxial material testing system (LIGAO, HF-9002) equipped with a 100N load cell. For the tensile test, the hydrogels used were dumbbell-shaped (20 mm long and 3 mm wide). For the compression test, the hydrogels used were cylindrical specimens (25 mm in diameter and 12 mm in height).
[0159] Figure 1 It is the red laser pen irradiation phenomenon corresponding to the Li / Al-LDH solution placed for different time periods. When the newly prepared Li / Al-LDH solution is irradiated with a red laser pen, a bright red light path is formed in the solution, with a very obvious Tyndall effect. This indicates that the size of the Li / Al-LDH nanosheets is between 1-100nm and is evenly distributed in the solution. However, when the solution is left for a week and then irradiated with a red laser pen, the Tyndall effect is significantly weakened. This indicates that the Li / Al-LDH nanosheets begin to gradually stack and increase in size. After the solution has been left for a month, the Li / Al-LDH nanosheets are stacked into visible white flake sizes. At this point, when irradiated with a red laser pen, the Tyndall effect has completely disappeared. This indicates that the Li / Al-LDH nanosheets can no longer be evenly dispersed in the solution. Therefore, it is the best choice to use the newly prepared Li / Al-LDH solution with Tyndall effect for the next step of hydrogel synthesis.
[0160] Figure 2 This is a schematic diagram of the preparation process of PXL nano-conductive hydrogel. In the first step, the freshly prepared Li / Al-LDH solution with Tyndall effect and deionized water are added to a beaker, and then acrylamide (AM) monomer and xanthan gum (XG) powder are slowly added thereto, and after magnetic stirring, ultrasonic treatment is performed in an ice water bath to remove bubbles to obtain a microemulsion viscous liquid; in the second step, the photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) and the cross-linking agent N,N-methylenebisacrylamide (MBA) are added, and after mixing, magnetic stirring is performed to obtain a PXL hydrogel precursor solution; in the third step, the mixed solution is quickly poured into a polytetrafluoroethylene (PTFE) mold with the desired shape, and then the mold is covered with a glass sheet to remove bubbles and isolate the air; finally, in the fourth step, in-situ polymerization is performed under ultraviolet light for 30 minutes to obtain PXL nano-conductive hydrogel.
[0161] Figure 3 This is the sandwich structure diagram of the PXL pressure sensor. It can be seen that the PDMS film as the upper and lower dielectric layers and the PXL nano-conductive hydrogel as the central sensing layer are well combined. Due to the softness of the encapsulation material PDMS, it can achieve synchronous expansion and contraction deformation with the monitoring part. In addition, PDMS protects the hydrogel, weakens the influence of other external factors, reduces the wear and loss of water, and is convenient for long-term use under complex external conditions.
[0162] Figure 4 The SEM images of different hydrogels obtained in Comparative Example 1, Comparative Example 2 and Example 1 are shown in FIG. Figure 4a) Large pores and smooth thick pore walls due to the close packing and high hydrogen bond density between chains. When XG was added, the pore walls of the PX hydrogel prepared in Comparative Example 2 became thicker than those of PAM ( Figure 4 b). This is because the penetration and entanglement of the XG network and the PAM network structure effectively fill the network pores of the hydrogel, promoting the structure to become denser. With the further addition of Li / Al-LDH prepared in step 2 of Example 1, the interaction between the components is enhanced, and the pore density of the hydrogel is significantly increased, showing a more compact cross-linked structure ( Figure 4 c), which is beneficial to improve the mechanical strength. In addition, after local magnification, the special conductive network structure we want can also be seen inside the pores, which achieves excellent conductivity while enhancing the mechanical properties.
[0163] Figure 5 The PXL obtained in Example 1 13.33% TEM image and element distribution diagram of nano-conductive hydrogel. Figure 5 As shown in a, in PXL 13.33% Obvious lattice fringes can be observed in the TEM image of the hydrogel, indicating that the Li / Al-LDH nanosheets are uniformly distributed in the porous hydrogel. In addition, the in situ SAED spectrum also shows the presence of Li / Al-LDH in the PXL hydrogel, and the encapsulation of the PX hydrogel does not affect the structure and particle size of the Li / Al-LDH nanosheets. In addition, well-crystallized Li / Al-LDH lattice fringes can be observed in the PXL hydrogel ( Figure 5 b). The lattice spacing d = 0.76 nm corresponds to the (002) crystal plane of Li / Al-LDH crystal. 13.33% The SAED and TEM images of the hydrogel not only reveal the crystallographic behavior of Li / Al-LDH nanosheets, but also provide strong evidence for the successful encapsulation of Li / Al-LDH nanosheets. Figure 5 c) shows the uniform distribution of C, N, Li, and Al elements, which demonstrates the formation of a semi-IPN in the hydrogel.
[0164] Figure 6 The infrared spectra of different hydrogels obtained in Comparative Example 1, Comparative Example 2 and Example 1 are shown. For PAM hydrogel, at 3342 cm -1 and 3191cm -1 The different absorption peaks at 1647cm correspond to the asymmetric and symmetric stretching vibrations of -NH2. -1 and 1604cm -1 The bands at 3469 cm-1 in XG correspond to the stretching vibration of carbonyl C=O and the bending vibration of NH. -1The absorption band at 1616cm is attributed to OH stretching vibration. -1 The characteristic peak at 1411 cm -1 The absorption peak at is due to the -COO - Compared with XG and PAM, there is no new absorption peak in PX, indicating that no chemical reaction occurs between XG and PAM. However, it can be observed that the stretching vibration absorption peak of the -OH group of PX hydrogel shifts to 3330 cm -1 This is due to the formation of new intermolecular hydrogen bonds between XG and PAM. After adding Li / Al-LDH, due to the presence of Al in Li / Al-LDH 3+ , Al 3+ It can complex with -OH, resulting in a reduction in -OH functional groups, thereby reducing the number of hydrogen bonds. -1 The -OH stretching vibration band at the PXL 13.33% The C=O stretching vibration absorption peak of XG in the hydrogel is at 1616 cm -1 and 1658cm -1 This is due to the -COO - Li in Li / Al-LDH + and Al 3+ A metal coordination bond is formed.
[0165] Figure 7 The PXL obtained in Example 1 13.33% XRD pattern of hydrogel. From this we can see that although PXL 13.33% The peak intensity of the XRD pattern of the hydrogel is slightly weakened or even partially disappeared, but its main XRD peak can still correspond one-to-one with the prepared Li / Al-LDH and Li / Al-LDH standard card, which also proves that Li / Al-LDH is successfully embedded in the PX hydrogel.
[0166] Figure 8 The tensile stress-strain curves of the hydrogels of different components prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Example 1 and Comparative Example 5 and the PXL prepared in Example 1 are shown in FIG. 13.33% The test diagram of various compression mechanical properties of pressure sensor. Figure 8As shown in a, we can see that the tensile elongation of pure PAM hydrogel reaches 1200%, but its tensile strength is only 20kPa. After adding XG, the tensile strain and fracture strength of the hydrogel are improved. At this time, the tensile strain is 1630% and the fracture strength is 60kPa. This is due to the introduction of XG rigid double helix chain into the PAM flexible chain structure to form a rigid-flexible SIPN structure. The abundant hydroxyl and carboxyl groups on the XG molecular chain combine with the amide groups on the PAM molecular chain to form a large number of hydrogen bonds. The diversity of interactions increases, which promotes the enhancement of the polymer network and significantly improves the mechanical strength of the hydrogel. When different amounts of Li / Al-LDH are added as nanofillers to the PX hydrogel, the tensile strain and fracture strength of the hydrogel are improved again. Among them, the PXL with a Li / Al-LDH content of 0.4g and a mass percentage of 13.33% 13.33% The tensile elongation of the hydrogel reached 2350%, and its tensile strength was greatly enhanced to 210 kPa. This is because the selected LiAl-LDH nanofiller contains abundant edge metal ions (Li + and Al 3+ ), which can produce coordination interactions with -C(O)NH2 in PAM hydrogel; among which the rich Al 3+ It can also react with the hydroxyl groups in the hydrogel to generate a complex with hydroxyl groups as ligands; and the hydroxyl groups on the Li / Al-LDH nanosheets can also produce hydrogen bond interactions with the -C(O)NH2 in the PAM chain, further improving the mechanical strength of the hydrogel. In addition, the coordination interaction between the abundant carboxyl groups in the XG side chain and the abundant metal ions in Li / Al-LDH can also stabilize the double helix structure of XG, which is icing on the cake in terms of enhancing the mechanical strength of the hydrogel. Figure 8 b, 8c and 8d, for PXL 13.33% The pressure sensor has been tested for various compression mechanical properties, from which it can be seen that PXL 13.33% The hydrogels have an excellent elastic range and a high elastic limit, as well as a high elastic modulus and excellent creep resistance.
[0167] Fig. 9 The PXL prepared in Example 1 13.33% The compression electrical performance test diagrams of the pressure sensor. (a) is the compression sensitivity under different pressure ranges; (b) is the 3600-cycle compression test; (c) is the PXL 13.33% Pressure response time and recovery time of pressure sensor; (d) and (e) are PXL 13.33% The relative resistance change of the pressure sensor under low and high frequencies; (f) is PXL 13.33%The relative resistance change of the pressure sensor under different pressures. The above electrical performance tests show that the pressure sensor has extremely high sensitivity and detection accuracy to pressure, and has good linearity in resistance change within the pressure range, and exhibits excellent pressure-sensitive characteristics in terms of response / recovery time, repeatability, stability, etc., giving full play to the advantages of the pressure sensor.
[0168] Fig.10 The PXL prepared in Example 1 and Example 2 was placed for seven days. 13.33% Tensile stress-strain curve of the hydrogel and the PXL prepared in Example 2 after seven days of storage 13.33% Electrical performance test diagram of pressure sensor. (a) is PXL 13.33% (a) The tensile stress-strain curves of the hydrogel before and after being placed at room temperature at 25°C for seven days; (b) The tensile stress-strain curves of the PXL after being placed at room temperature for seven days 13.33% Sensitivity of the pressure sensor; (c) PXL after being placed at room temperature for seven days 13.33% The relative resistance change of the pressure sensor under different deformations. It can be seen that PXL 13.33% The decrease in the mechanical strength of the hydrogel is negligible ( Fig.10 a), it still maintains a high sensitivity of 4.74 ( Fig.10 b), and can also remain stable in electrical performance tests under different deformations ( Fig.10 c) This proves that PXL 13.33% The pressure sensor can be used normally and stably even if it is left exposed at room temperature for more than one week.
[0169] In addition, by comparing Example 1, Example 2, and Comparative Examples 1 to 5, it can be seen that when the added volume ratio of the Li / Al-LDH solution with Tyndall effect and deionized water in step 3 of the method of the present invention is 1:1, the two have a synergistic effect and can synergistically improve the relevant performance of the prepared product.
[0170] Fig.11 This is the overall connection framework diagram of the three-point pressure sensing smart insole. Fig.11 As shown, by designing the copper wire circuit and PXL 13.33% The hydrogel is assembled, and then the plastic film with PET as the base material and EVA as the adhesive is used to seal the insole. Then the data is connected to the AD converter through a wire to read the data, and then sent to the STM32 microcontroller for data processing. Finally, the data is transmitted through the Bluetooth module, and the real-time visualization of the plantar pressure distribution is achieved through the self-developed APP. The smart insole is highly integrated, light, flexible, and easy to wear, which solves the various defects of traditional plantar pressure distribution monitoring equipment.
[0171] Fig.12 This is the real-time plantar pressure distribution status monitoring diagram of the three-point pressure sensing smart insole on the sole of the foot. From this we can see that the APP can receive the pressure data transmitted by the Bluetooth module in real time, and convert it into the color depth of the color block through the self-written JAVA program for display, to indicate the real-time plantar pressure distribution status of the three-point pressure sensing smart insole on the sole of the foot. We tested the plantar pressure distribution diagram of people in three states: normal standing, leaning forward, and leaning backward. It can be seen that the plantar pressure distribution status monitored by the APP in real time is accurate and stable, which can reflect the physical condition of the person and is very intelligent.
[0172] At present, some resistive pressure sensors have been manufactured, such as by screen printing a pressure sensitive film on ceramics, photolithography on the surface of a silicon wafer to form a pressure sensitive resistor, assembling an alloy with an elastic element to form a pressure strain gauge, etc. to achieve pressure sensing, but the preparation process of these methods is usually complicated and time-consuming, which hinders its practical application in large-scale production. The pressure sensor in the present invention is simple and reliable to manufacture, does not require complicated process steps, avoids losses in the manufacturing process, and is easy to achieve mass production.
[0173] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.
Claims
1. A pressure sensor based on Li / Al-LDH enhanced polyacrylamide / xanthan gum double network nano-conductive hydrogel, characterized in that: The steps include: Step 1, dissolving LiCl, AlCl3 and urea in deionized water, mechanically stirring until they are completely dissolved, to obtain a Li / Al-LDH precursor solution; Step 2, placing the Li / Al-LDH precursor solution in a reflux device for reflux, using a red laser pen to irradiate the solution to track the reaction progress, and ending the reaction before the Tyndall effect of the solution disappears to obtain a Li / Al-LDH solution; Step 3, adding the freshly prepared Li / Al-LDH solution with Tyndall effect and deionized water into a beaker, and then slowly adding acrylamide monomer and xanthan gum powder thereto, stirring magnetically and then performing ultrasonic treatment in an ice water bath to remove bubbles, to obtain a microemulsion viscous liquid; Step 4, adding a photoinitiator 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone and a crosslinking agent N,N-methylenebisacrylamide, mixing and magnetically stirring to obtain a PXL hydrogel precursor solution; Step 5, quickly transferring the PXL hydrogel precursor solution into a polytetrafluoroethylene mold, and polymerizing in situ under ultraviolet light to obtain the PXL nano-conductive hydrogel; Step 6, mixing the polydimethylsiloxane glue A and glue B, stirring mechanically to make them uniform, and removing bubbles by ultrasound to obtain a PDMS precursor solution; Step 7, pouring the PDMS precursor liquid into a polytetrafluoroethylene mold, and then placing it in a vacuum oven, and curing it at high temperature to obtain a PDMS film; Step 8: Cut the prepared PDMS film into squares, and then assemble it with the PXL nano-conductive hydrogel. After assembly, fix the wires at both ends to achieve electrical connectivity, and finally obtain a pressure sensor with a sandwich structure based on the PXL nano-conductive hydrogel.
2. The pressure sensor according to claim 1, characterized in that: The ratio of LiCl:AlCl3:urea:deionized water added in step 1 is 1:3.2:14.4:50 g:g:g:mL, wherein AlCl3 is slowly added in a fume hood at the end and mechanically stirred for 15 min to obtain a Li / Al-LDH precursor solution; Alternatively, the temperature of the reflux device in step 2 is controlled at 97°C.
3. The pressure sensor according to claim 1, characterized in that: The total volume of the Li / Al-LDH solution with Tyndall effect and deionized water added in step 3 was in a ratio of 20:3 to acrylamide in mL:g, and the ratio of acrylamide to xanthan gum was in a ratio of 3:0.15 in g:g; magnetic stirring was applied for 6 hours; the ice-water bath temperature was 0°C, and the ultrasonic frequency was 10kHz for 10 minutes to remove bubbles, thereby obtaining a microemulsion-like viscous liquid.
4. The pressure sensor according to claim 1, characterized in that: The ratio of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone: N,N-methylenebisacrylamide: acrylamide added in step 4 was 9:2.4:3 in mg:mg:g; magnetic stirring was performed for 1 hour to obtain PXL n Hydrogel precursor solution.
5. The pressure sensor according to claim 1, characterized in that: Step 5: PXL n After the hydrogel precursor solution is quickly transferred to the polytetrafluoroethylene mold, it should be sealed with a glass slide to isolate oxygen; it should be irradiated under a 20W ultraviolet lamp with a wavelength of 365nm for 30 minutes to obtain PXL in situ polymerization. n Nano-conductive hydrogel; Its shape is a cylindrical hydrogel with a diameter of 25 mm and a height of 5 mm.
6. The pressure sensor according to claim 1, characterized in that: In step 6, the volume ratio of polydimethylsiloxane (PDMS) A glue and B glue is 10:1, wherein A glue is dimethylsiloxane and B glue is a crosslinking agent and accelerator; mechanical stirring for 2 hours; ultrasonic treatment at a frequency of 10 kHz for 30 minutes to remove bubbles, to obtain a PDMS precursor solution; Alternatively, in step 7, the temperature of the vacuum oven is controlled at 50° C., and high-temperature curing is performed for 12 hours to obtain a PDMS film.
7. The pressure sensor according to any one of claims 1 to 6, characterized in that: The size of the PDMS film cut in step 8 is a 3 cm × 3 cm square; the sandwich structure uses the PDMS film as the upper and lower dielectric layers, PXL n Nano-conductive hydrogel is used as the central sensing layer, and then the two ends are connected with wires to finally obtain PXL n Pressure sensor.
8. Application of the pressure sensor according to any one of claims 1 to 7 in a three-point pressure sensing smart insole for the sole of the foot.
9. A three-point pressure sensing intelligent insole for the sole of the foot made by using the pressure sensor according to any one of claims 1 to 7, characterized in that: The assembly method of the three-point pressure sensing intelligent insole comprises the following steps: By designing copper wire circuits and PXL n The hydrogel is assembled and then sealed with a plastic film using PET as the base material and EVA as the adhesive to form an insole; then it is connected to an AD converter, a single-chip computer, a Bluetooth module, a voltage regulator module and a lithium battery through wires; finally, the program is written to obtain a three-point pressure-sensing smart insole for the sole of the foot.
10. The functional APP of the three-point pressure sensing smart insole of claim 9, characterized in that: The functional APP can monitor the user's plantar pressure distribution status in real time through the mobile phone, evaluate the user's sports health, and thus achieve disease prevention.